A laboratory X-ray microscopy setup using a field emission electron source and micro-structured reflection targets - Stahlhut, P.; Ebensperger, T.; Zabler, S.; Hanke, R. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2014)
We present a computed tomography (CT) setup for materials characterization with significantly improved resolution as compared to state of the art mirco- or sub extgreekm-CT systems. The system presented here is composed of a customized JEOL JSM7100-F scanning electron microscope with a thermal field-emission electron source allowing to focus an intense electron beam onto specially designed micro-structured reflection target thereby further reducing the size of the X-ray source spot by reducing the electron interaction zone and thus reducing image blur at high magnifications. With the proposed setup geometric magnifications up to M = 1000 and spatial resolutions down to 100 nm can be achieved. We also demonstrate the phase contrast capabilities of the setup.
EAM Import::2019-03-13